Sequence motifs recognized by the casposon integrase of Aciduliprofundum boonei - Béguin, Pierre (Nucleic Acids Res, 2019)
Casposons are a group of bacterial and archaeal DNA transposons encoding a specific integrase, termed casposase, which is homologous to the Cas1 enzyme responsible for the integration of new spacers into CRISPR loci. Here, we characterized the sequence motifs recognized by the casposase from a thermophilic archaeon Aciduliprofundum boonei. We identified a stretch of residues, located in the leader region upstream of the actual integration site, whose deletion or mutagenesis impaired the concerted integration reaction. However, deletions of two-thirds of the target site were fully functional. Various single-stranded 6-FAM-labelled oligonucleotides derived from casposon terminal inverted repeats were as efficiently incorporated as duplexes into the target site. This result suggests that, as in the case of spacer insertion by the CRISPR Cas1–Cas2 integrase, casposon integration involves splaying of the casposon termini, with single-stranded ends being the actual substrates. The sequence critical for incorporation was limited to the five terminal residues derived from the 3′ end of the casposon. Furthermore, we characterize the casposase from Nitrosopumilus koreensis, a marine member of the phylum Thaumarchaeota, and show that it shares similar properties with the A. boonei enzyme, despite belonging to a different family. These findings further reinforce the mechanistic similarities and evolutionary connection between the casposons and the adaptation module of the CRISPR–Cas systems.